Kathleen Sprows Cummings. A Saint of Our own: How the Quest for a Holy Hero Helped Catholics Become American. Chapel Hill : The University of North Carolina Press, 2019, 320 pp. - Suárez, Ana Lourdes (Ciencias sociales y religión, 2020)
The book presents a meticulous study of the intricate process by which some Catholics in the United States were “officially” recognized as saints of the country. It presents the historical and socio-religious contexts that accompanied the complex canonization process of Elizabeth Seton, Frances Cabrini, Katharine Drexel and John Neumann; as well as those of Kateri Tekakwitha, Rose Philippine Duchesne, Junípero Serra, among others. The questions that guide the book are: What motivated Catholics in the United States to seek to have the Vatican recognize some of its faithful as "holy"? What fueled the need for those figures? How did that need change over time and why? How and why did the attributes highlighted in the figures proposed for the arduous process challenge North American religious culture? Why did some postulations succeed and others not?